Vasopressin V1a receptor gene and voluntary exercise: Insights from humans and animal models - Shizue Masuki; Eri Sumiyoshi; Mayuko Morikawa; Hiroshi Nose (Japanese Society of Physical Fitness and Sports Medicine, 2015)
There is no long-term exercise training regimen with high adherence and effectiveness for middle-aged and older people that is broadly available in the field. To solve this problem, we developed an exercise training regimen comprised of interval walking training (IWT) and an IT network system that only requires minimal staff support. We found that adherence to the 22-month IWT program was relatively higher than other previously reported long-term exercise programs requiring more personnel support and that the program was accompanied by greater improvements in lifestyle-related disease risk factors and physical fitness in middle-aged and older people. Moreover, when congenital and acquired factors affecting adherence were assessed, we found that baseline body mass index and gender for all subjects, as well as smoking and vasopressin V1a receptor polymorphisms for men, were independent determinants of adherence to the IWT program. To elucidate the mechanism underlying the effect of V1a receptor polymorphisms on adherence to an exercise program, we assessed whether voluntary locomotion was impaired in mice genetically deficient in V1a receptors (V1a KO). We found that voluntary locomotion in wild-type mice was more probable after cerebral activation, while in V1a KO mice the probability was markedly reduced with no suppression of baroreflex control of heart rate during cerebral activation. Moreover, the findings in V1a KO mice were confirmed after local infusion of a V1a receptor antagonist into the nucleus tractus solitarii of the wild-type mice. Thus, central V1a receptors play an important role in facilitating voluntary exercise and thereby contribute to adherence to the IWT program.